Non-polio enteroviruses in faeces of children diagnosed with acute flaccid paralysis in Nigeria (2017)
The need to investigate the contribution of non-polio enteroviruses to acute flaccid paralysis (AFP) cannot be over emphasized as we move towards a poliovirus free world. Hence, we aim to identify non-polio enteroviruses recovered from the faeces of children diagnosed with AFP in Nigeria.Ninety-six isolates, (95 unidentified and one previously confirmed Sabin poliovirus 3) recovered on RDcell culture from the stool of children <15 years old diagnosed with AFP in 2014 were analyzed. All isolates were subjected to RNA extraction, cDNA synthesis and three different PCR reactions (one panenterovirus 5′-UTR and two different VP1 amplification assays). VP1 amplicons were then sequenced and isolates identified. Results: 92.71% (89/96) of the isolates were detected by at least one of the three assays as an enterovirus. Precisely, 79.17% (76/96), 6.25% (6/96), 7.30% (7/96) and 7.30% (7/96) of the isolates were positive for both, positive and negative, negative and positive, as well as negative for both the 5′-UTR and VP1 assays, respectively. In this study, sixty-nine (69) of the 83 VP1 amplicons sequenced were identified as 27 different enterovirus types. The most commonly detected were CV-B3 (10 isolates) and EV-B75 (5 isolates). Specifically, one, twenty-four and two of the enterovirus types identified in this study belong to EV-A, EV-B and EV-C respectively. This study reports the circulating strains of 27 non-polio enterovirus types in Nigerian children with AFP in 2014 and Nigerian strains of CV-B2, CV-B4, E17, EV-B80, EV-B73, EV-B97, EV-B93, EV-C99 and EV-A120 were reported for the first time. Furthermore, it shows that being positive for the 5′-UTR assay should not be the basis for subjecting isolates to the VP1 assays.